2018
DOI: 10.1038/s41419-018-1204-7
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1-suppressed autophagy promotes nasopharyngeal carcinoma cell invasion and metastasis by PI3K/AKT signaling activation

Abstract: Annexin A1 (ANXA1) is dysregulated in the various tumors. However, the role and mechanism of ANXA1 in the cancers are poorly understood. In this study, we first showed a clinically positive correlation between ANXA1 and autophagy-associated protein SQSTM1 expression in nasopharyngeal carcinoma (NPC) and ANXA1-regulating SQSTM1 expression through autophagy, and further demonstrated that ANXA1 inhibited BECN1 and ATG5-dependent autophagy in the NPC cells. Using phospho-kinase antibody array to identify signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 46 publications
3
75
0
Order By: Relevance
“…Alli-Shaik et al analyzed mammary epithelial cells from ANXA1-hybrid and ANXA1-deficient mice by quantitative phosphorylation proteomics and found that most ANXA1-responsive phosphorylation changes occurred in proteins involved in cytoskeletal reorganization, which favors (30). Overexpression of ANXA1 is often associated with EMT in some aggressive cancers (31,32). TGF-β/Smad signaling plays an important role in the progression of EMT in breast cancer, in which phosphorylation of Smad2 triggers the formation of a complex between Smad2 and Smad4, resulting in nuclear translocation of the Smad2/Smad4 complex and subsequent gene transcription (12,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Alli-Shaik et al analyzed mammary epithelial cells from ANXA1-hybrid and ANXA1-deficient mice by quantitative phosphorylation proteomics and found that most ANXA1-responsive phosphorylation changes occurred in proteins involved in cytoskeletal reorganization, which favors (30). Overexpression of ANXA1 is often associated with EMT in some aggressive cancers (31,32). TGF-β/Smad signaling plays an important role in the progression of EMT in breast cancer, in which phosphorylation of Smad2 triggers the formation of a complex between Smad2 and Smad4, resulting in nuclear translocation of the Smad2/Smad4 complex and subsequent gene transcription (12,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…AKT/NF-κB signaling pathway has been reported to play an important role in tumor cell proliferation, differentiation, and metastasis. 18 We examined the activation of AKT.…”
Section: Cisplatin Attenuated the Metastasis Promoting Capacity Of Camentioning
confidence: 99%
“…Breast tumor cell proliferation and migration were enhanced when ANXA1 was added, 9 and ANXA1-suppressed autophagy promoted nasopharyngeal carcinoma cell invasion and metastasis. 10 Another study reported that during oxygen-glucose deprivation, ANXA1 promoted microglial activation and migration. 11 We therefore determined whether exogeneous ANXA1-induced SC cellular proliferation and migration, thus, leading to nerve regeneration.…”
mentioning
confidence: 99%